Semi-structural VAR and unobserved components models to estimate finance-neutral output gap - Gábor Kátay; Lisa Kerdelhué; Matthieu Lequien (Publications Office of the European Union, 2020)
The paper assesses the impact of adding information on financial cycles on the output gap estimates for eight advanced economies using two unobserved components models: a reduced form extended Hodrick-Prescott filter, and a standard semi-structural unobserved components model. To complement these models, a semi-structural vector autoregression model is proposed in which only supply shocks are identified. The accuracy of the output gap estimates is assessed based on their performance in predicting recessions. The models with financial variables generally produce more accurate output gap estimates at the expense of increased real-time volatility. While the extended Hodrick-Prescott filter is particularly appealing for its real-time stability, it lags behind the two semi-structural models in terms of forecasting performance. The vector autoregression model augmented with financial variables features the best in-sample forecasting performance, and it has similar real-time prediction capabilities to the semi-structural unobserved components model. Overall, financial cycles appear to be relevant in Japan, Spain, the UK, and - to a lesser extent - in the US and in France, while they are relatively muted in Canada, Germany, and Italy.
Keywords: C32; E32; E44; G01; O11; O16; 330; unobserved components model; semi-structural VAR; output gap; financial cycle; sustainable growth; credit; house prices; advanced economies